2022
DOI: 10.5802/crmath.329
|View full text |Cite
|
Sign up to set email alerts
|

On the monoidal invariance of the cohomological dimension of Hopf algebras

Abstract: We discuss the question of whether the global dimension is a monoidal invariant for Hopf algebras, in the sense that if two Hopf algebras have equivalent monoidal categories of comodules, then their global dimensions should be equal. We provide several positive new answers to this question, under various assumptions of smoothness, cosemisimplicity or finite dimension. We also discuss the comparison between the global dimension and the Gerstenhaber-Schack cohomological dimension in the cosemisimple case, obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In particular, for 𝐹 = 𝐾 * 𝐾 = diag(𝑞 −1 , 1, 𝑞), 𝑞 ∈ ℝ + , it turns out that the second Hochschild cohomology of Pol(𝑈 + 𝐾 ) ≅ (𝐹) with trivial coefficients is one-dimensional; this was the missing piece in [20], where the second Hochschild cohomology of all other free unitary quantum groups was determined. Theorem B also yields explicitly for every generic matrix 𝐹 a (one-dimensional) bimodule 𝑀 with H 3 ((𝐹), 𝑀) ≠ 0, which confirms that the cohomological dimension of (𝐹) is three; a fact Bichon conjectured in [11,Remark 5.15] and proved by more abstract considerations in [12,Theorem 8.1].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…In particular, for 𝐹 = 𝐾 * 𝐾 = diag(𝑞 −1 , 1, 𝑞), 𝑞 ∈ ℝ + , it turns out that the second Hochschild cohomology of Pol(𝑈 + 𝐾 ) ≅ (𝐹) with trivial coefficients is one-dimensional; this was the missing piece in [20], where the second Hochschild cohomology of all other free unitary quantum groups was determined. Theorem B also yields explicitly for every generic matrix 𝐹 a (one-dimensional) bimodule 𝑀 with H 3 ((𝐹), 𝑀) ≠ 0, which confirms that the cohomological dimension of (𝐹) is three; a fact Bichon conjectured in [11,Remark 5.15] and proved by more abstract considerations in [12,Theorem 8.1].…”
Section: Introductionsupporting
confidence: 63%
“…In particular, for F=KK=prefixdiag(q1,1,q)$F = K^*K = \operatorname{diag}(q^{-1},1,q)$, qR+$q\in \mathbb {R}^+$, it turns out that the second Hochschild cohomology of prefixPol(UK+)scriptH(F)$\operatorname{Pol}(U_{K}^+)\cong \mathcal {H}(F)$ with trivial coefficients is one‐dimensional; this was the missing piece in [20], where the second Hochschild cohomology of all other free unitary quantum groups was determined. Theorem B also yields explicitly for every generic matrix F$F$ a (one‐dimensional) bimodule M$M$ with H3(Hfalse(Ffalse),M)0$\mathrm{H}^3(\mathcal {H}(F),M)\ne 0$, which confirms that the cohomological dimension of scriptHfalse(Ffalse)$\mathcal {H}(F)$ is three; a fact Bichon conjectured in [11, Remark 5.15] and proved by more abstract considerations in [12, Theorem 8.1]. Theorem Let FGLn(C)$F\in \operatorname{GL}_n(\mathbb {C})$ be generic.…”
Section: Introductionmentioning
confidence: 64%
“…Theorem 4.3 therefore ensures that if A has bijective antipode, then A * w A s (n) is projective as a left and right A * n -module. This was shown and used in the proof of [4,Theorem 8.4], using [7], under the additional assumption that k = C and that A is a compact Hopf algebra.…”
Section: Proposition 35 Assume That a ⊂ H Is Right Faithfully Flatish...mentioning
confidence: 93%
“…(3) Pointed Hopf algebras are free over their Hopf subalgebras: this was shown by Radford [14]. (4) The celebrated Nichols-Zoeller theorem [12] ensures that finite-dimensional Hopf algebras are free over their Hopf subalgebras (5) Chirvasitu [6] has shown that if H is cosemisimple, then it is faithfully flat over its Hopf subalgebras. The case when A ⊂ H is only a coideal subalgebra is also of high interest in view of quotient theory, but here the situation is not that we can reasonably expect that faithful flatness holds, since even in the commutative case it is easy to find natural coideal subalgebras over which the Hopf algebra is not faithfully flat (for example k[x, y] ⊂ O(SL 2 (k)).…”
Section: Introductionmentioning
confidence: 99%